Matrilines in Neolithic cattle from Orkney, Scotland reveals complex husbandry patterns of ancestry. (August 2017) - Fraser, Sheena; Elsner, Julia; Derek Hamilton, W.; Sayle, Kerry L.; Schlumbaum, Angela; Bartosiewicz, László
Abstract: mtDNA, isotopic and archaeozoological analyses of cattle teeth and bones from the Late Neolithic site of Links of Noltland, Orkney, Scotland revealed these animals followed similar grazing regimes but displayed diverse genetic origins and included one cattle skull that carried an aurochs (wild cattle) genetic haplotype. Morphometric analyses indicate the presence of some cattle larger than published dimensions of Neolithic domestic cattle. Several explanations for these finding are possible but may be the evidence of a complex pattern of domestic cattle introductions into Neolithic Orkney and interbreeding between domestic and wild cattle. Highlights: Aurochs genetic haplotype recovered from Late Neolithic cattle skull, Orkney Diverse genetic origins revealed for Late Neolithic domestic cattle, Orkney Some post-cranial bones from Late Neolithic domestic cattle, Orkney, with larger dimensions than expected Late Neolithic cattle, Orkney grazing on similar pastureland may include aurochs/domestic cattle hybrids